Протокол для забезпечення інформаційної безпеки в системі "Розумний будинок" - Ляшенко, О. С.; Гольцев, Д. О. (ХНУРЕ, 2019)
In this paper, we propose an implementation option for a protocol for secure data exchange between smart home network devices. The models necessary to solve the problem of ensuring secure interaction using lowresource cryptography in a smart home network are considered. A software implementation of the proposed protocol was developed using the example of a smart home network.
Keywords: розумний будинок; протокол інформаційна безпека; моделі загроз